2018
DOI: 10.1111/acel.12715
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial ATP synthase is a shared drug target for aging and dementia

Abstract: SummaryAging is a major driving force underlying dementia, such as that caused by Alzheimer's disease (AD). While the idea of targeting aging as a therapeutic strategy is not new, it remains unclear how closely aging and age‐associated diseases are coupled at the molecular level. Here, we discover a novel molecular link between aging and dementia through the identification of the molecular target for the AD drug candidate J147. J147 was developed using a series of phenotypic screening assays mimicking disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
127
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(139 citation statements)
references
References 38 publications
6
127
1
1
Order By: Relevance
“…: 1146963-51-0) when screening compounds from plants with the ability to reverse brain aging cells and molecular marker. Several reports suggest that J147 can reverse memory deficits, enhance the production of new brain cells, and retard the progression of Alzheimer's disease in rats 16,17 .Related the study of molecular mechanisms have found that J147 combines with the proteins mitochondrial proteins via ATP synthase, there by promoting aging cells, mice and fruit flies to look younger 17 . Besides, Lian et al 18 reports that J147 improves the depression-like behavior in mouse models caused by chronic stress, and its mechanism may involve the regulation of cAMP/pCREB/ BDNF pathway.…”
mentioning
confidence: 99%
“…: 1146963-51-0) when screening compounds from plants with the ability to reverse brain aging cells and molecular marker. Several reports suggest that J147 can reverse memory deficits, enhance the production of new brain cells, and retard the progression of Alzheimer's disease in rats 16,17 .Related the study of molecular mechanisms have found that J147 combines with the proteins mitochondrial proteins via ATP synthase, there by promoting aging cells, mice and fruit flies to look younger 17 . Besides, Lian et al 18 reports that J147 improves the depression-like behavior in mouse models caused by chronic stress, and its mechanism may involve the regulation of cAMP/pCREB/ BDNF pathway.…”
mentioning
confidence: 99%
“…Among the numerous pathogenic proteins identified, mitochondrial ATP synthase (mATP synthase) has been recently explored as a viable therapeutic target, having been implicated in the progression of the disease. [10] Decreased activity of mitochondrial electron transport chain enzymes or F 1 F 0 -ATPase (ATP synthase complex V) is likely to alter brain ATP synthesis and lead to the production of reactive oxygen species, which in intense cases, causes neuronal cell death. [11,12] ATP synthase is also implicated in the neurofibrillary degeneration of AD and depicted by the cytosolic accumulation of this mitochondrial protein.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Reports by Goldberg et al revealed that J147 (N-(2,4-dimethylphenyl)-2,2,2-trifluoro-N'-[(E)-(3-methoxyphenyl)methylidene]acetohydrazide), a derivative of curcumin, therapeutically binds to the α-F1 subunit of mATP synthase (ATP5A) with high affinity and allosterically modulates its activity (Figure 1). [10] JI47 successfully slowed down progression of AD, countered memory loss and enhances the generation of new brain cells, hence it was described as the 'elixir of life'.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations